Application of a novel microalgae‐film based air purifier to improve air quality through oxygen production and fine particulates removal. Issue 4 (20th November 2018) - Lu, Qian; Ji, Chengcheng; Yan, Yuping; Xiao, Yan; Li, Jun; Leng, Lijian; Zhou, Wenguang
Abstract: BACKGROUND: Low oxygen content and high density of airborne fine particulates in closed environments are serious problems threatening people's health. Herein a novel concept of using microalgae for air purification is proposed, and approaches, including the construction of a condensed microalgae film and the use of hydrogel, to realize this concept in a real‐world application are discussed. RESULTS: The results demonstrated that moisture loss, which limited O2 production and fine particulates removal, is a serious technical barrier to the durable use of this air purifier. With the addition of hydrogel, moisture loss of microalgae film in 8 h was reduced to 24.76%. Comparison of the contributions of hydrogel and microalgae indicated that in this air purifier, microalgae mainly contributed to fine particulates removal while hydrogel enhanced the performance of microalgae film by alleviating the moisture loss. Studies on the mechanisms proved that fine particulates removal by microalgae film is mainly driven by negative surface charge on microalgae cells. CONCLUSIONS: This study showed that qa microalgae‐film based air purifier performed well in oxygen production and fine particulates removal. In a real‐world application, to properly operate this air purifier, moisture content and pH value of the microalgae film should be strictly controlled. © 2018 Society of Chemical Industry